2012
DOI: 10.1002/adma.201202422
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐Range Refractive Index Control of Organic Semiconductor Films Toward Advanced Optical Design of Organic Optoelectronic Devices

Abstract: A large refractive index difference of 0.58 is demonstrated in organic semiconductor films toward advanced optical design of organic optoelectronic devices. Efficient control of light propagation is shown by distributed Bragg reflectors (DBRs) consisting of organic semiconductor films. The DBRs also show photoconductivity, indicating the promising possibility of active control of both charges and light by the organic semiconductors themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Molecular orientation is already recognized as a key factor influencing device performance (1, 2, 4, 5, 10-15, 37, 38) and our results provide a predictive tool for choosing the deposition temperature needed to produce the desired orientation, effectively adding a dimension to device design. The ability to predictably tune refractive indices across a wide range is analogously useful in applications that rely on redirection of light, such as waveguides or antireflective coatings (39). Although the results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular orientation is already recognized as a key factor influencing device performance (1, 2, 4, 5, 10-15, 37, 38) and our results provide a predictive tool for choosing the deposition temperature needed to produce the desired orientation, effectively adding a dimension to device design. The ability to predictably tune refractive indices across a wide range is analogously useful in applications that rely on redirection of light, such as waveguides or antireflective coatings (39). Although the results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,20 At appropriate substrate temperatures, many of these materials will likely form stable glasses 44 and there are open questions about the transformation mechanism in this geometry. The active layers in OLEDs are thin (30-50 nm) and are in contact on both sides with other solid films.…”
Section: Transformation Mechanism For Thicker Films and Films Withoutmentioning
confidence: 99%
“…[ 14 ] For example, Yokoyama et al showed a change of up to 0.58 in refractive index by using a multilayer stack. [ 15 ] In this work, we demonstrated that a multi-alternating 4,4′,4′′-Tris(N-3-methylphenyl-N-phenylamino) triphenylamine (m-MTDATA)/F 16 CuPc stack exhibits ohmic conductivity which is observed neither in the corresponding bilayer nor bulk heterojunction. Figure 1 shows the current density-voltage (J-V) characteristics of two devices with respectively 1 (dashed line) and 30 (solid line) units of "m-MTDATA/F 16 CuPc" bilayers (same total thickness of 300 nm) in the confi guration of ITO/1 or 30 units of bilayer (300 nm)/BPhen (8 nm)/Al.…”
mentioning
confidence: 97%